Methodology for ground-fault protection of personnel in industrial power systems (2017)
"Shock hazards are a matter of concern in industrial power systems, that occur with low frequency, yet may have fatal consequences on people. Since only 5mA are needed for a person to feel a current flow through his body, protection against higher values is essential to avoid electrocutions. Moreover, the elevated costs associated to the loss of a person are not worthwhile, so a proactive solution shall be implemented. The National Electrical Code existing regulation of ground faults demands an assured equipment grounding conductor program to regularly test the integrity of the grounding conductor. By doing so, the continuity of the grounding conductor is guaranteed and the chance of occurrence of ground faults is reduced. The problem of this solution is that it does not work continuously in the time frame and is not intended to interrupt ground faults. Instead, industrial GFCIs (Ground-Fault Circuit Interrupters) are suited to improve the safety of personnel, for it is continuously sensing the circuit to detect ground faults and interrupt them. Implicitly, these devices fill the role of the assured equipment grounding conductor program. Besides, these devices are very sensitive due to the magnitude of the ground fault currents, therefore it is extremely important to implement them correctly. For that reason, the different cases of the device operation are shown in this document and supported with the results of a simulation in ATPDraw. Finally, a methodology for the proper implementation of GFCIs in industrial power systems is presented."--Tomado del Formato de Documento de Grado